Соціальна безпека – домінанта національних інтересів країни в контексті сталого розвитку (концептуальний підхід) - Куценко, В.І.; Гаращук, О.В.; Топчій, О.О. (Економіка природокористування і сталий розвиток, 2019)
Досліджено теоретичні та методологічні аспекти соціальної безпеки в контексті сталого розвитку. Розкрито сутність цієї категорії та її складових, а також найважливіші чинники, які впливають на її рівень. Оцінено стан соціальної безпеки в Україні та визначено можливі загрози. Обґрунтовано підходи до формування умов для соціальної безпеки, що сприятиме сталому соціально-економічному розвитку. The article notes that humanity has realized the need for changes in the social paradigm, in particular in the context of the transition to sustainable development. In this regard, the theoretical and methodological aspects of social safety in the context of sustainable development are investigated; reveals the essence of the category "social safety" and its components. It is emphasized that social safety, which covers all spheres of human life – social, economic, environmental and guarantees the safety of society from various types of threats. The most important factors affecting the provision of social safety are also considered, the leading place among which is occupied by those that are of a socio-economic nature. These factors ensure the avoidance of social deformations and imbalances in human life, the infringement of his vital interests.
An assessment is made of the situation in Ukraine regarding social safety, and in this regard, possible threats are identified. Among these threats, it is especially noted that Ukraine stands out for its low birth rates and a high mortality rate, that is, it has a significant excess of mortality over fertility. An important statement is that the formation of social safety is not only the overcoming of existing problems and threats, but, above all, the formation of tools to prevent and protect society from their onset. Considerable attention is paid to the substantiation of approaches to the formation in our country of conditions for ensuring social safety, taking into account the principles of sustainable development of human civilization and its scientifically sound balance. Among these principles are noted – the acquisition of new knowledge by employees; priority development of the social sphere; implementation of an active regulatory policy of the state to ensure social guarantees, which should take into account the concentration of state resources on the satisfaction of priority social interests; creating an effective mechanism for achieving social safety. All this should contribute to sustainable socio-economic development.